ANALYSIS OF MARKETING MIX ON CUSTOMER SATISFACTION: EMPIRICAL STUDY OF PURCHASING DECISION OF EAST NUSA TENGGARA LOCAL PRODUCT - Sonya Lisabel Malelak; Budi Setiawan; Silvana Maulidah (Socio-Economics/Agribusiness Department, 2021)
The purpose of this study is to analyze the effect of marketing mix on purchasing decisions of East Nusa Tenggara local products, to analyze the effect of marketing mix on consumer satisfaction of local products and to analyze the indirect effect of marketing mix on research satisfaction. The results showed that the variable price, place, promotion directly had a positive and significant effect on the purchasing decision variable. The product variable directly has a positive but insignificant effect. variable product, price, place, promotion directly have a positive and significant effect on customer satisfaction variables. The purchasing decision variable is not indirectly a mediation for the product variable and the consumer satisfaction variable. The purchase decision variable is not indirectly a mediation for the price variable and the consumer satisfaction variable. The purchase decision variable is not indirectly a mediation for the place variable and the consumer satisfaction variable. The purchasing decision variable is indirectly mediating for the promotion variable and the customer satisfaction variable.